Kultur Damai Berbasis Tradisi Pela Dalam Perspektif Psikologi Sosial - Roubrenda N. Ralahallo (Faculty of Psychology, Universitas Gadjah Mada, 2009)
Conflict and violence was the destructive reality that showed reduction and alienated of existence humanity. The essence of human being has destruction because dominance of egoism of people’s without care value of victim community. Because of that condition, the basic need to create a culture of peace as constructive reality that connected relationship between all of people is urgently. On the level individual and group, the acceptance of “the other‐self” as him/herself has destroy the wall of differences which always be source of conflict and violence. The fusion identity “we” (ingroup) and “them” (outgroup) has establish common ingroup identity as “us” in recategorization process that contribution to reduction negative aspect seems like prejudice, discrimination and stereotype. This research involve four subject with age 20‐30 years old, genre as masculin and feminin, and they have a comprehensive science about pela tradition. Other informant like a King of negeri, Kapitan negeri and all of people also involve in this research. Qualitative method with ethno‐phenomenology approach is use in this research with observation and interview as method and procedure to collect data. The result of this research showed that culture of peace can be found in local wisdom as pela tradition. The basic idea in this tradition is a common identity “saudara/orang basudara” which has calling as “ela”. Pscychological dynamics occur in this perspective because the word of “ela” to contain a constructive and positive meaning that arranged relation between the groups Rohomoni‐Tuhaha. Implementation of values the culture of peace has been seen in the behavioral “saudara pela” that mutual constructive, trust, respect. This fact could be found in Molluccas conflict at 1999‐2004, pela tradition can be the media reconciliation between two groups Moslem and Christian.